2016
DOI: 10.1590/1982-0216201618218115
|View full text |Cite
|
Sign up to set email alerts
|

Análise integral da produção científica brasileira em motricidade orofacial: estado da arte e perspectivas futuras

Abstract: A complete review of Brazilian scientific articles on orofacial myology (OM) published in the last 10 years was conducted to describe, categorize and quantitatively analyze studies in the field of OM. Data were collected from all Brazilian journals on speech-language and hearing sciences published between 2005 and 2015. All articles were reviewed and categorized according to the year of publication, type of article and subject area. Furthermore, all studies conducted on humans that reported quantitative data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(16 reference statements)
1
0
0
3
Order By: Relevance
“…The level of scientific evidence of the selected studies ranged from three to five, with a predominance of level three, highlighting the need for further research in this area, with randomized controlled trials and systematic literature reviews. This finding is in agreement with a survey of the Brazilian scientific production in the field of Orofacial Motricity that, although presenting a growing number of publications, showed that studies predominantly present cross-sectional designs and low levels of scientific evidence (27) .…”
Section: Discussionsupporting
confidence: 91%
“…The level of scientific evidence of the selected studies ranged from three to five, with a predominance of level three, highlighting the need for further research in this area, with randomized controlled trials and systematic literature reviews. This finding is in agreement with a survey of the Brazilian scientific production in the field of Orofacial Motricity that, although presenting a growing number of publications, showed that studies predominantly present cross-sectional designs and low levels of scientific evidence (27) .…”
Section: Discussionsupporting
confidence: 91%
“…A literatura apresenta várias revisões (narrativas, integrativas, sistemáticas) da produção científica da área sobre uma determinada temática, ou sobre um campo de atuação profissional 7,8 . Mas a produção de conhecimento tem sido objeto de análises mais abrangentes, que consideram tendências ou apontam avanços e lacunas observadas na produção da área 6 .…”
Section: Métodounclassified
“…No entanto, a classificação das disfunções e distúrbios em MO é ainda uma fragilidade da clínica fonoaudiológica, sendo alvo das pesquisas na área (Tomaz-Morais et al, 2016). O uso da tecnologia pode auxiliar ao atrelar um parâmetro quantitativo à subjetividade na avaliação miofuncional para que, dessa forma, a condução terapêutica seja eficiente e objetiva.…”
Section: Introductionunclassified